Influence of the Circadian Timing System on Tacrolimus Pharmacokinetics and Pharmacodynamics After Kidney Transplantation - Fontova, Pere; Colom, Helena; Rigo-Bonnin, Raül; van Merendonk, Lisanne N.; Vidal-Alabró, Anna; Montero, Nuria; Melilli, Edoardo; Meneghini, Maria; Manonelles, Anna; Cruzado, Josep M.; Torras, Juan; Grinyó, Josep Maria; et al. (Frontiers in Pharmacology, 2021)
Introduction: Tacrolimus is the backbone immunosuppressant after solid organ transplantation. Tacrolimus has a narrow therapeutic window with large intra- and inter-patient pharmacokinetic variability leading to frequent over- and under-immunosuppression. While routine therapeutic drug monitoring (TDM) remains the standard of care, tacrolimus pharmacokinetic variability may be influenced by circadian rhythms. Our aim was to analyze tacrolimus pharmacokinetic/pharmacodynamic profiles on circadian rhythms comparing morning and night doses of a twice-daily tacrolimus formulation. Methods: This is a post-hoc analysis from a clinical trial to study the area under curve (AUC) and the area under effect (AUE) profiles after tacrolimus administration in twenty-five renal transplant patients. Over a period of 24 hours, an intensive sampling (0, 0.5, 1, 1.5, 2, 3, 4, 6, 8, 12, 12.5, 13, 13.5, 14, 15, 20, 24 hours) was carried out. Whole blood and intracellular tacrolimus concentrations and calcineurin activity were measured by UHPLC-MS/MS. Results: Whole blood and intracellular AUC12-24h and Cmax achieved after tacrolimus night dose was significantly lower than after morning dose administration (AUC0-12h) (p<0.001 for both compartments). AUE0-12h and AUE12-24h were not statistically different after morning and night doses. Total tacrolimus daily exposure (AUC0-24h), in whole blood and intracellular compartments, was over-estimated when assessed by doubling the morning AUC0-12h data. Conclusion: The lower whole blood and intracellular tacrolimus concentrations after night dose might be influenced by a distinct circadian clock. This significantly lower tacrolimus exposure after night dose was not translated into a significant reduction of the pharmacodynamic effect. Our study may provide conceptual bases for better understanding the TDM of twice-daily tacrolimus formulation.